Cystic lesions of the pancreas: current trends in approach and management. Issue 1025 (23rd December 2010) - Vyas, Soumil; Markar, Sheraz; Ezzat, Tarek M; Ajit, Abraham
Abstract : The more frequent deployment of cross-sectional imaging for various abdominal conditions has resulted in an increased detection of cystic pancreatic lesions, particularly cystic pancreatic neoplasms. Cystic pancreatic lesions may be neoplastic or non-neoplastic. They may appear radiologically similar and often present a diagnostic dilemma; they need to be diagnosed and differentiated with accuracy in order to offer optimum treatment. Some of the cystic neoplasms are potentially malignant and have a wide spectrum of histological variation from the frankly benign 'adenomas' to invasive adenocarcinomas .When identified, these cystic lesions need a systematic work up and a diagnostic algorithm should be followed to its logical conclusion. This article reviews these cystic lesions of the pancreas, neoplastic and pseudocysts, and aims to update readers with the current trends in their diagnosis and management.